(untitled) - Howell-Carey, Chantal (Hoboken, N.J., 2006)
Make Money in Abandoned Properties provides readers with new ideas and vital techniques for every aspect of abandoned property investment, from identifying the right properties to successfully negotiating with owners. There is enormous potential in abandoned properties, and Chantal and Bill Carey explain everything you need to know to get started: Why owners abandon properties; Finding abandoned properties with profit potential; Locating owners and qualified buyers; Writing a foolproof offer for the property; Counter-offers and negotiations; Negotiating with owners in foreclosure; Financing techniques for abandoned properties; Rehabbing abandoned properties for instant equity; Optioning abandoned properties; Finding motivated partners for your deals; Investment strategies that focus on abandoned property; Dealing with owners in bankruptcy; Closing deals and using escrow.
Keywords: Real estate investment,Abandonment of property,Real property; Purchasing; United States,United States,United States